Epistemologi Revolusi Ilmiah Thomas Kuhn (Pemikiran dan Relevansinya Terhadap Kajian Keilmuan Islam): Pemikiran dan Relevansinya Terhadap Kajian Keilmuan Islam - Rahmat Ramadhan, Rajendra; M. Guntur Sandi Pratama; Valid Fathony , Bimba (IAIN Datuk Laksemana Bengkalis, Indonesia, 2024)
Thomas Kuhn is a philosopher and scientist who is unique in giving names to the terms he uses in his scientific models. Kuhn used the term